Structural correction of nonlinear dynamics of frequency-controlled induction motor drives - Vladimir L. Kodkin; Aleksandr Sergeevich Anikin; Aleksandr Aleksandrovich Baldenkov (International Journal of Power Electronics and Drive Systems (IJPEDS), 2020)
Frequency analysis of processes in the frequency-controlled induction motor drive s, as in automatic control systems with dynamic non-linearities, are presented in this paper. For the first time, dynamic formulas of transfer functions of a torque driver in an induction motor with frequency control, taking into account the slip and frequency of the stator voltage, are proposed. Methods for constructing families of frequency characteristics of such electromechanical systems with “frozen” but different values of the frequency of the stator voltage and slip are described. The frequency characteristics corresponding to these transfer functions are constructed in the Simulink application of the MatLab software. Based on results of the analysis the structural correction methods that improve the dynamics of such nonlinear systems are proposed. The nonlinear transfer functions obtained in this work made it possible to substantiate structural solutions that linearize frequency-controlled electric drives and significantly increase their efficiency. This paper is an example of how the initial complicated (but more accurate) interpretation of nonlinearity allowed us to find a new best solution to the problem of controlling a complex dynamic object.